The state of being in love as means of expanding cognition in Martin Eden by Jack London, Maurice by E.M. Forster and En ausencia de Blanca by Antonio Muñoz Molina - Kołakowski, Marcin (Revista Chilena de Literatura, 2020)
The article analyzes the literary manifestations of the emotional state of “being in love” and its cognitive value in terms of personal development of the main characters in three novels: Martin Eden by Jack London, Maurice by Edward Morgan Forster and En ausencia de Blanca by Antonio Muñoz Molina. The main methodological perspective is based on the theorizations of Francesco Alberoni (who purports that “being in love” constitutes a cognitive vehicle) and is broadened by investigations by J. Ortega y Gasset, E. Fromm, J. Kristeva, and others on the matter. In order to illustrate the three potential paths of character’s cognitive development (or its lack), the article analyzes the love discourse in the above mentioned novels, the storyline (which is determined by the emergence and development of infatuation) as well as the impact this state has on existential decisions made by the main characters.